IMPORTANCE OF DETERMINING LIQUID LEVEL WITH THE HELP OF AN ULTRASOUND SENSOR USING AN ARDUINO MICROCONTROLLER IN AGRICULTURE (International journal of artificial intelligence, 2025)
This article will consider modern hardware and software for water level control, which is one of the most pressing problems in agriculture. The hardware and software complex offered in this work differs from other water table management systems in a number of advantages. The automatic water level monitoring system proposed in this study is versatile and easy to use. The hardware and software system in question can be used in monitoring processes of various sectors of the economy.